Legal Supervision of China's Internet Insurance Information Security under the Background of Digital Economy - Marina V. CHARAEVA; Laibing SUN (Communications of International Proceedings, 2020)
In the context of the digital economy, while promoting the development of network insurance, it has brought unprecedented risks to the traditional insurance model. The data involved is usually very private and important identity information. Once leaked and used illegally, it will cause more serious problems. s consequence. This has brought huge challenges to personal information security and supervision. Therefore, with regard to the information security of the Internet insurance market in the context of the digital economy, China can only learn from the successful experience of Western developed countries, combined with the actual situation in China, and on the basis of strengthening security technology research, adhere to the law as the main supervision method and formulate With the improvement of personal information protection laws and the promotion of the establishment of an Internet insurance credit system, the information security issues of China’s Internet insurance can be effectively resolved.
Keywords: Digital Economy; Insurance Information Security; Legal Supervision; Risks; Internet Financial Platforms; Internet Insurance Market.